2020
DOI: 10.1177/2058739220942626
|View full text |Cite
|
Sign up to set email alerts
|

A new treatment for ulcerative colitis: Intracolonic Bifidobacterium and xyloglucan application

Abstract: Ulcerative colitis (UC) pathogenesis includes the altered gut microbiota, environmental factors, and human immune and genetic predisposition. Recently, its association with reduced bifidobacteria quantity in the microbiota is reported. Xyloglucan, a plant-based prebiotic oligosaccharide, causes increase in bifidobacteria quantity. In this article, we share the results of our UC cases treated by intracolonic single-dose administration of Bifidobacterium animalis subsp. lactis and xyloglucan combination. Intraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Lactis-BB12 led to rapid mucosal healing in an ulcerative colitis patient. 7,19 This effect was related to the IL-17 inhibitory effect of the BB-12 strain. Zuo et al 20 showed that patients with COVID-19 had a significantly disrupted gut microbiome, characterised by enrichment of opportunistic pathogens and depletion of beneficial commensal bacteria.…”
Section: Bifidobacteria In the Management Of Covid-19mentioning
confidence: 92%
See 4 more Smart Citations
“…Lactis-BB12 led to rapid mucosal healing in an ulcerative colitis patient. 7,19 This effect was related to the IL-17 inhibitory effect of the BB-12 strain. Zuo et al 20 showed that patients with COVID-19 had a significantly disrupted gut microbiome, characterised by enrichment of opportunistic pathogens and depletion of beneficial commensal bacteria.…”
Section: Bifidobacteria In the Management Of Covid-19mentioning
confidence: 92%
“…24 Interestingly, IL-17 has been shown to be a proangionesis cytokine, especially in the context of cancer metastases. 7 For all of these reasons the administration of a single high dose of an appropriate strain of bifidobacterium (such as BB-12, or infantis) and especially in patients with gastrointestinal symptoms (diarrhoea, abdominal pain, vomiting), may be postulated to have a role in the management of coronavirus infected patients. In support of this proposal it should be noted that Jayawardena 25 reported that bifidobacterium probiotic strains either reduced the severity or shortenes the duration of viral infections; in another report, Bifidobacterium infantis reduced the duration of acute respiratory infections illness in children and adults.…”
Section: Bifidobacteria In the Management Of Covid-19mentioning
confidence: 99%
See 3 more Smart Citations